FGDNOGRAPHY: Discussing a Topic in the Nature of the Topic - Wijaya, Bambang Sukma (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2016)
FGDnography is a research method that combines data collection techniques through FGD (Focus Group Discussion) with ethnographic research approaches. In FGDnography, group discussion about a topic occurs in a venue that follows the theme discussed. The nuance, situation, environment, ambiance, and attributes inherent in the location support the topic. Discussions become more lively, real, and relevant. As a result, the insights obtained are more natural, authentic, and meaningful. Several aspects deserve attention in FGDnography, including natural-ness, discuss-ness, interactive-ness, responsive-ness, meaningfulness, and experience-ness.   FGDnografi: Mendiskusikan Sebuh Topik sesuai Karakter TopiknyaFGDnografi adalah metode penelitian yang menggabungkan teknik pengumpulan data melalui FGD dengan pendekatan riset etnograpfi. Dalam FGDnografi, diskusi kelompok tentang topik diselenggarakan di tempat yang sesuai dengan topik yang dibahas, sehingga nuansa, situasi, lingkungan, ambians, dan atribut-atribut yang melekat di tempat tersebut mendukung isu yang dibahas. Diskusi topik menjadi lebih hidup, nyata, dan relevan. Hasilnya, insights yang diperoleh lebih natural, otentik, dan meaningful. Ada beberapa aspek yang patut diperhatikan dalam FGDnography, di antaranya aspek kealamiahan (natural-ness), kediskusian (discuss-ness), interaktivitas (interactive-ness), responsivitas (responsive-ness), kebermaknaan (meaningfulness), dan kepengalamanan (experience-ness). To cite this article (7th APA style):Wijaya, B. S. (2016). FGDnography: Discussing a Topic in Nature of the Topic. Journal Communication Spectrum: Capturing New Perspectives in Communication, 6(2), 176-200